Penguatan Keterampilan Problem Solving Melalui Model PBL Pada Sistem Perawatan Permesinan Kapal - Taruna Taruna; Masringgit Marwiyah (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2026)
Problem-solving skills are essential competencies for maritime engineering students, particularly in the field of ship machinery maintenance. This study investigates the effectiveness of the Problem-Based Learning (PBL) model in enhancing students’ problem-solving abilities in the Ship Machinery Maintenance Systems course at Politeknik Negeri Medan. A quantitative approach employing a quasi-experimental pretest–posttest control group design was utilized, involving 62 students divided into an experimental group (n = 31, PBL) and a control group (n = 31, conventional instruction). The research instrument consisted of a 20-item problem-solving test encompassing four key indicators: problem identification, formulation of alternative solutions, solution implementation, and evaluation and verification. Data were analyzed using normalized gain (N-Gain) scores and independent sample t-tests. The experimental group achieved a posttest mean of 84.52 (SD = 6.73) with an N-Gain of 0.74 (high category), significantly outperforming the control group, which obtained a mean of 71.38 (SD = 7.21) and an N-Gain of 0.43 (medium category). Statistical analysis revealed a significant difference between the two groups (t(60) = 7.82, p < 0.001). Among the assessed indicators, problem identification demonstrated the highest improvement (N-Gain = 0.78), while evaluation and verification showed the lowest gain (N-Gain = 0.68). These findings indicate that PBL is considerably more effective than conventional teaching methods in fostering problem-solving competencies in ship machinery maintenance